Program “Sekolah Sak Ngajine” dan Implikasinya terhadap Pendidikan Agama Islam Holistik di Sekolah Dasar Islam: “Sekolah Sak Ngajine” Program and Its Implications for Holistic Islamic Education in Islamic Elementary Schools - Lisna Yunita; Rosidin; Rahmatullah; Mochamad Nurcholiq (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to describe the implementation and implications of the Sekolah Sak Ngajine Program in enhancing holistic Islamic Religious Education (PAI) at Miftahul Ulum Islamic Elementary School, Klemunan, Wlingi, Blitar. Methods: The research employs a qualitative approach with a single case study design. Data were collected through observation, in-depth interviews with the principal, teachers, and students, as well as document analysis. Data analysis followed the Miles and Huberman model (data reduction, data display, and conclusion drawing). The program implementation consisted of two main stages: (1) The conceptual/planning stage included Program Planning, Foundation Consolidation, Curriculum Integration, and Procedure Development; (2) The practical stage involved Socialization, Execution/Implementation, and Monitoring & Evaluation. The program had positive implications across three holistic education domains: (a) Increased understanding of PAI materials (Qur'an, Fiqh, Aqidah-Akhlaq); (b) Enhanced student character, responsibility, spiritual awareness, and worship discipline; (c) Improved skills in reading the Qur'an with tartil and practicing worship (ablution, prayer). Sekolah Sak Ngajine Program has proven effective as an integrative model for realizing holistic PAI, aligning with Ki Hajar Dewantara's